1983
DOI: 10.2307/214331
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of American Rice Consumption 1955 and 1980

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. American Geographical Society is collaborating with JSTOR to digitize, preserve and extend access to Geographical Review. HE opening sentence in "The American Heritage Cookboo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Rice consumption provides a window on yet another set of shifts in diet and attitudes. J.R. Shortridge and B.G. Shortridge (1998b) show through careful analysis of producer and shipper data (most rice consumed in the USA is grown and shipped there) that before the 1960s little rice was eaten outside the producer regions in the Deep South, or in ethnic enclaves where rice was a customary item in the diet.…”
Section: Food and Food Issuesmentioning
confidence: 99%
“…Rice consumption provides a window on yet another set of shifts in diet and attitudes. J.R. Shortridge and B.G. Shortridge (1998b) show through careful analysis of producer and shipper data (most rice consumed in the USA is grown and shipped there) that before the 1960s little rice was eaten outside the producer regions in the Deep South, or in ethnic enclaves where rice was a customary item in the diet.…”
Section: Food and Food Issuesmentioning
confidence: 99%
“…He identifies six "contempormy diet regions"-the No1theast, the South, the Midwest, the Southwest, the Interior West, and the Pacific West-and discusses the forces which have helped shape food consumption in each of these regions. Like Shmtridge and Shortridge (1998b), Pillsbmy argues that the West Coast-and again California most significantly-is where the nation's ideas about food and cuisine develop.…”
Section: By Richardmentioning
confidence: 99%
“…It is not known what is commonly eaten at home in the region as no studies have addressed this question. Additionally, studies have shown that is difficult to accurately measure daily eating habits(Shortridge and Shortridge 1998b;Thompson and Newman 1999).…”
mentioning
confidence: 99%